Under pressure : cooking sous vide - Keller, Thomas, 1955-; Beno, Jonathan; Lee, Corey, 1977-; Rouxel, Sebastien; Heller, Susie; Ruhlman, Michael, 1963-; Vogler, Amy (Artisan, 2008)
"[A] source of instruction, technique and recipes for anyone who wants to experience the new ideas sous vide makes possible."- Resumé vydavatel
Includes index.
Keywords: vaření sous-vide; kuchařství; sous-vide cooking; cookery; elektronické knihy; kuchařské recepty; electronic books; cookbooks